Parallel mediation of mindfulness and psychological distress self-stigma in the relationship between mental health self-stigma and psychological distress among young adults in Malaysia - Ma'rof, Aini Azeqa; Abdullah, Haslinda; Azmi, Syasya Firzana (Human Resource Management Academic Research Society, 2024)
This study explores the parallel mediating roles of mindfulness and psychological distress self stigma in the relationship between mental health self-stigma and psychological distress among young adults in Malaysia. Utilizing a cross-sectional survey of 413 young adults from various educational institutions and community settings, the research employs established instruments to measure the constructs. The findings indicate that mental health self-stigma is a significant predictor of psychological distress, with mindfulness and psychological distress self-stigma serving as crucial mediators. Young adults with lower levels of mental health self stigma who engage in mindfulness practices and have reduced psychological distress self stigma are more likely to experience lower levels of psychological distress. This highlights the importance of promoting mindfulness practices and addressing psychological distress self stigma to reduce the adverse effects of mental health self-stigma. Practical strategies suggested include implementing mindfulness-based interventions, such as Mindfulness Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT), and conducting psychoeducational and cognitive-behavioral programs to reduce self-stigma. In conclusion, the study provides empirical evidence on the mediating roles of mindfulness and psychological distress self-stigma in the relationship between mental health self-stigma and psychological distress. By understanding these dynamics, mental health professionals and organizations can develop targeted strategies to support young adults in managing psychological distress, ultimately improving their psychological wellbeing. These findings offer valuable insights for both academics and practitioners in mental health intervention and youth development.